(untitled) (Annals of Medical Research, 2022)
Aim: Pulmonary Embolism (PE) is an obstructive illness of the pulmonary artery system that occurs in varying degrees and locations and is caused by embolization of thrombus or non-thrombotic substances that originate in the deep veins of the lower limbs. Pulmonary embolism is a preventable disease that has a high probability of recurrence, high mortality, and morbidity. The differential diagnosis and clinical treatment of pulmonary embolism have a very important place in emergency service applications. The purpose of the present study was to retrospectively examine the patients who applied to Inonu University Turgut Ozal Medical Center Emergency Service between 2014 and 2019 and were diagnosed with PE. Materials and Methods: In the present study, the data were collected retrospectively from a total of 144 patients including 80 female and 64 male patients who applied to Turgut Ozal Medical Center (TOMC) Emergency Department with the complaints of sweating, chest pain, cough, hemoptysis, and syncope between January 2014 and August 2019 and diagnosed with PE with the I-26 diagnostic code according to the ICD 10 coding system. The quantitative data obtained from the patients were summarized as mean and standard deviation or median, as well as minimum and maximum, and the qualitative data were summarized as numbers and percentages. The compatibility of the data with the normal distribution was evaluated with the Kolmogorov Smirnov test and the homogeneity of the variances was examined with the Levene test. The Independent Samples t-test and Mann Whitney U test were used to analyze the data. The IBM SPSS Statistics version 26.0 for Windows package program was used in the analyses. A P<0.05 value was taken as statistically significant. Results: No significant differences were detected in terms of systolic arterial blood pressure, diastolic arterial blood pressure, and laboratory variables of leukocyte, lymphocyte, neutrophil, neutrophil/lymphocyte, and platelet/lymphocyte ratios between the PE patients with and without right ventricular dilatation on ECHO. Statistically significant differences were detected for platelet, MPV, and CRP between the patients with and without right ventricular dilatation in ECHO. Conclusion: It is considered that these findings will provide data on the prognosis and general condition of patients and will help the clinician to make an earlier and easier prediction about the clinical prognosis of patients.